Large mediastinal haematoma after paraoesophageal hernia repair. Issue 12 (5th December 2019) - Finnegan, Tim; MacDonald, Nicholas; Gianis, Thomas; Senkowski, Christopher
Abstract : Mediastinal haematoma is a rare complication of laparoscopic paraoesophageal hernia repair with few documented cases in the current literature. Presentation of this unique clinical problem can range from extrinsic oesophageal obstruction to life-hreatening cardiac tamponade and therefore, warrants further discussion of at-risk population aetiology, diagnosis and successful management strategies. We present the case of a 71-year-old woman who underwent laparoscopic paraoesophageal hernia repair with nissen fundoplication complicated by severe dysphagia on postoperative day 12. Further evaluation with oesophagram and CT imaging revealed a large mediastinal haematoma with near obstruction of the distal oesophagus. This was managed successfully with laparoscopic transhiatal washout and drainage.